A Systematic Review : Cost-Effectiveness of Targeted Therapy and Immunotherapy Compared with Chemotherapy in Cancer - Oktaviani Eka Soehartono (International Journal of Health Engineering and Technology, 2026)
Cancer remains one of the leading causes of death globally, with increasingly high treatment costs, particularly for targeted therapy and immunotherapy. In resource-limited healthcare systems such as Indonesia, cost-effectiveness analysis (CEA) is essential for determining efficient therapeutic options. This study aims to evaluate scientific evidence regarding the cost-effectiveness of targeted therapy and immunotherapy compared with conventional chemotherapy in cancer patients. The study employed a systematic literature review approach based on the PICO framework and PRISMA guidelines. Literature was obtained from Google Scholar, PubMed, and ScienceDirect databases, including articles published between 2015 and 2025, written in English, and available in full-text open access. Five original research articles that met the inclusion criteria were analyzed narratively. The findings indicate that not all advanced therapies are economically efficient compared with conventional chemotherapy. Tislelizumab as monotherapy was found to be more cost-effective than combination therapy for liver cancer. In HER2-positive breast cancer, the TCH regimen was more cost-efficient than AC-TH. Additionally, local immunotherapies such as sintilimab and toripalimab demonstrated lower ICER values compared with global therapies in several developing countries. In conclusion, therapies that are clinically effective are not always economically efficient. Therefore, integrating pharmacoeconomic considerations is important in cancer treatment decision-making within healthcare services.